Religiusitas dan Rasa Bersalah pada Remaja di Sman 1 Pantai Cermin Kabupaten Solok - Ifani Candra; Clin Abdila; Isna Asyri Syahrina (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
Guilt is a conscious emotion that causes adolescents to feel sorry, uncomfortable as a result of violating a social norm and religiosity is the belief in the existence of forces outside of oneself that regulate life and life in the universe. This study aims to explore and determine the relationship between religiosity and guilt in adolescents at SMAN 1 Pantai Cermin, Solok Regency. The independent variable (x) in this study is religiosity and the dependent variable (y) is guilt. The measuring instrument used in this study is the scale of religiosity and guilt scale. The sampling technique in this study used a simple random sampling technique. The sample in this study amounted to 165 students of SMAN 1 Pantai Cermin Solok Regency. Test the validity and reliability in this study using the alpha cronbach technique. The item discriminatory index on the religiosity scale moves from rix= 0.327 to rix= 0.839 with a reliability coefficient of = 0.926 while the guilt scale moves from rix= 0.327 to rix= 0.816 with a reliability coefficient of = 0.930. Based on data analysis, it can be concluded that there is a very significant relationship between religiosity and guilt, with a correlation value (r) of 0.511 with a significant level of 0.000 which means the hypothesis is accepted. This shows that with the proposed hypothesis there is a very significant positive relationship between religiosity and guilt in adolescents at SMAN 1 Pantai Cermin, Solok.